Pandemic and sport: The challenges and implications of publicly financed sporting venues in an era of no fans - Mayer, M.; Cocco, A. R. (Public Works Management & Polic, 2020)
Professional sport leagues suspended their seasons as Covid-19 became a part of daily life in March 2020, leaving stadiums and arenas across the country empty. Lost in the hysteria of the global pandemic has been the consequences that a lack of sports may have on many state and local government budgets in their efforts to fund their share of sport-related infrastructure expenditures. This commentary examines the history of public sector stadium financing in the U.S. and focuses on two current examples in Arlington, Texas and Las Vegas, Nevada. The discussion highlights innovative measures and risk-mitigation strategies implemented after the Great Recession. Public sector finance challenges due to Covid-19 are discussed, before offering recommendations on strategies to limit public infrastructure risk surrounding sport facilities moving forward.